Development of a materials requirement planning(MRP) software (2012)
"Lack of affordable, efficient, and user friendly inventory management tools, for adequate planning has been identified as a major cause of the high inventory cost in many Nigerian manufacturing firms. This study focuses on the development of a Materials Requirements Planning (MRP) that can be used by the local industries for inventory management in a job shop manufacturing environment. Four types of lot sizing techniques were analysed and MRP algorithms developed for each of these lot-sizing techniques. A process of Bill of Materials (BOM) explosion was developed and incorporated. An overall flow chart of the MRP process sequences and a graphical user interface (GUI) based software of the MRP process was developed using Microsoft Visual basic. Evaluation tests of the software were carried out using various products ranging from those with simple structure of single product to complex structure with multiple products sharing common items. The software was shown to be user friendly and allow for easy data input and output allowing for product structure to be saved and retrieved for future planning. "